Integrating AI and Innovative Materials in Modern Product Development: A Holistic Approach - Srikanth Raavi Venkata (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative integration of Artificial Intelligence (AI) and innovative materials in modern product development. It examines how AI-driven technologies, such as eye-tracking and emotional intelligence systems, are revolutionizing the way companies understand consumer preferences and design products. The article also delves into the growing importance of sustainable materials, including biodegradable plastics and eco-friendly alternatives like cork and popcorn-based packaging. The article highlights successful case studies by analyzing the synergies between AI-assisted design processes and sustainable material use and discusses the challenges and opportunities in adopting these advanced approaches. The article further investigates the potential future directions of this integration, considering its impact on consumer behavior and market trends. Ultimately, this article underscores the significant potential of combining AI and innovative materials to create products that are not only more aligned with consumer needs but also environmentally responsible, potentially reshaping entire industries and fostering a new era of sustainable, personalized product development.